The Controversy of the Book Waṣīyyat al-Muṣṭafā and Its Factors of Popularity in Hadith Studies - Ahmad Nurhamdani; Viki Junianto; Iqbal Nursyahbani; Mohammad Hamsa Fauriz (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The study of hadith in Indonesia has experienced significant development in the 17th century. This is marked by many scholars from the archipelago who authored and studied hadith texts in each generation. One of the key texts is Waṣiyyat al-Muṣṭafā. Although this text is popular, Waṣiyyat al-Muṣṭafā has a controversial aspect due to the presence of many fabricated hadiths and the ambiguity surrounding its authorship. This research aims to analyze the factors contributing to the popularity of Waṣiyyat al-Muṣṭafā in Indonesia. This study is qualitative in nature, utilizing literature review methods and employing an analysis based on Max Weber's theory of authority, which includes charismatic authority, traditional authority, and legal-rational authority. Additionally, the research uses the theory of printing or publication to analyze the factors behind the popularity of Waṣiyyat al-Muṣṭafā. The findings indicate that Waṣiyyat al-Muṣṭafā remains popular despite its controversial aspects, The presence of many fabricated hadiths and the ambiguity surrounding its authorship, largely due to influential community figures and their significant followings who engage in studying the text. Furthermore, the association of the text with Imam al-Sya’rani, known for his prominence in the field of hadith, is believed to have positively impacted its popularity. Additionally, the bureaucratic structure of pesantren (Islamic boarding schools) incorporates this text into its curriculum, and the printing industry has played a role in producing and disseminating Waṣiyyat al-Muṣṭafā throughout Indonesia.